On the L(2,1)-labeling of block graphs - Bonomo, Flavia (2011)
The distance-two labelling problem of graphs was proposed by Griggs and Roberts in 1988, and it is a variation of the frequency assignment problem introduced by Hale in 1980. An L(2, 1)-labelling of a graph G is an assignment of non-negative integers to the vertices of G such that vertices at distance two receive different numbers and adjacent vertices receive different and non-consecutive integers. The L(2, 1)-labelling number of G, denoted by λ(G), is the smallest integer k such that G has a L(2, 1)-labelling in which no label is greater than k.